Design of bacterial cellulose adhesives for wet tissue adhesion in oral cavity - Singh, Juhi (Nanyang Technological University, 2023)
Wet and dynamic environment of the oral cavity poses challenges for topical disease management approaches. Conventional treatments for oral wounds and infections exhibit weak adhesion to wet surfaces which results in short retention duration (6-8 hours), frequent dosing requirement and patient incompliance. Mucoadhesive drug delivery platforms are proposed herein for oral wound sites with soft tissue adhesion capability and ability to retain structural integrity in wet environments. Bacterial cellulose (BC) and photoactivated carbene-based bioadhesives are combined to yield flexible film platforms for interfacing soft tissues in dynamic, wet environments. Three platforms are presented in this thesis that are (1) layered composites, (2) fibrillated BC and carbene bioadhesive based hydrogels and (3) integrated adhesive patches. The first platform consists of carbene bioadhesive layered onto dry BC matrix and is referred to as 2-component layered composite. Structure-activity relationships evaluate UVA dose and hydration state with respect to adhesive strength on soft tissue mimics. The layered composite has an adhesion strength ranging from 7-17 kPa and duration exceeding 48 hours in wet conditions under sustained shear forces, while other mucoadhesives based on hydrophilic macromolecules exhibit adhesion strength of 0.5-5 kPa and last only a few hours. The work highlights the first evaluation of BC composites for mucoadhesive treatments in the buccal cavity. The layered composites however exhibit fracture in the adhesive matrix owing to non-homogenous carbene bioadhesive layer. Moreover, the composites could not be processed to dry formulation leading to diazirine instability in prolonged aqueous environments. The second platform addresses these limitations, aqueous composites made of fibrillated bacterial cellulose and photoactive bioadhesives are designed for soft epithelial surfaces. The composites comprise of uniform distribution of BC and carbene bioadhesive. The aqueous composites crosslink upon photocuring within a minute and exhibit transition from viscous to elastic adhesive hydrogels. The light-cured composites have shear moduli mimicking oral mucosa and other soft tissues. Tunable adhesion strength ranges from 3-35 kPa on hydrated tissue-mimicking surfaces (collagen film). The hydrogels could be freeze-dried and stored. However, part of material properties is lost upon rehydration. The previous two designs comprised of aqueous formulations presenting concerns with shelf-stability of the formulations. The third design, for the first time, presents dry, shelf-stable cellulose patches for convenient ready-touse application. The dry patches simultaneously remove tissue surface hydration while retaining carbene-based photocuring and offers on-demand adhesion. The dry patch prototypes are optimized by controlling BC/adhesive mole ratios and dehydration technique. The adhesion strength is higher than commercial denture adhesives on soft mucosal tissues. The structural integrity is maintained for a minimum of 7 days in aqueous environment. The patches act as selective nanoporous barrier properties against bacteria while allowing permeation of proteins. The results support the application of BC-based adhesive patches as a flexible platform for wound dressings, drug depots, or the combinations thereof.